2003
DOI: 10.1016/j.bbaexp.2003.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Novel vanadium-binding proteins (vanabins) identified in cDNA libraries and the genome of the ascidian Ciona intestinalis

Abstract: Ascidians, especially those belonging to the suborder Phlebobranchia, can accumulate high levels of vanadium. Vanadium-binding proteins (vanabins) were first isolated from a vanadium-accumulating ascidian, Ascidia sydneiensis samea, and then the vanabins were cloned, their expression was studied, and metal-binding assays were conducted. In order to unravel the mechanism of vanadium accumulation, we searched for vanabin-like genes in other animals, including other ascidians. A database search revealed five grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 23 publications
0
26
1
Order By: Relevance
“…At least six different types of blood cells have been described in ascidians (Wright, 1981;Rowley et al, 1984). Among these are the peculiar "vanadocytes," which are able to accumulate the vanadium dispersed in the seawater by means of recently characterized vanadiumbinding proteins (Michibata et al, 2002;Trivedi et al, 2003). This ability appears to be a unique feature of ascidians and, to date, has not been reported in any other system.…”
Section: Heart and Bloodmentioning
confidence: 99%
“…At least six different types of blood cells have been described in ascidians (Wright, 1981;Rowley et al, 1984). Among these are the peculiar "vanadocytes," which are able to accumulate the vanadium dispersed in the seawater by means of recently characterized vanadiumbinding proteins (Michibata et al, 2002;Trivedi et al, 2003). This ability appears to be a unique feature of ascidians and, to date, has not been reported in any other system.…”
Section: Heart and Bloodmentioning
confidence: 99%
“…Gene expression profiles based on EST analysis of fertilized eggs, embryos, and several tissues have been reported for some ascidian species (Makabe et al, 2001;Satou et al, 2002Satou et al, , 2003Yamaguchi et al, 2002Yamaguchi et al, , 2004, including A. sydneiensis samea and Ciona intestinalis, which contained 0.6 mM of vanadium in their blood cells (Michibata et al, 1986), and Halocynthia roretzi, which contained 0.01 mM of vanadium in their blood cells (Michibata et al, 1986). In our previous study, we successfully identified two novel Vanabins by EST analysis on the blood cells of A. sydneiensis samea (Yamaguchi et al, 2002(Yamaguchi et al, , 2004, as well as from C. intestinalis (Trivedi et al, 2003). However, related proteins and genes have not been annotated in the most vanadium-rich ascidian species A. gemmata, which contains 350 mM of vanadium in their blood cells (Michibata et al, 1991).…”
mentioning
confidence: 94%
“…Extensive efforts have been made to identify vanadium-binding proteins from vanadium-rich ascidians. Ion exchange column chromatography and immobilized metal ion affinity chromatography (IMAC) have been used in the identification of vanadium-binding proteins (Ueki et al, 2003a;Trivedi et al, 2003;Yamaguchi et al, 2004;Yoshihara et al, 2005Yoshihara et al, , 2008Yoshinaga et al, 2006;Michibata et al, 2007;Samino et al, 2012). The most prominent family of such proteins is the vanabins, which are novel vanadium-binding proteins ubiquitously found among vanadium-accumulating ascidians.…”
Section: Introductionmentioning
confidence: 99%